Digital Transformation in Public Administration: A Bibliometric Analysis - Daniela-Gabriela CAZAN (Communications of International Proceedings, 2022)
The purpose of this paper is to create a bibliometric analysis of digital transformation in public administration in order to analyze what are the strong relationships between digital transformation and the public sector. In this sense, the data was obtained from the Web of Science Core Collection and the entire analysis was by using VOSviewer software. The premise that digital transformation challenges innovation and it is a key to improving the quality of public services and a better life for citizens, was confirmed by the map which shows that digital transformation in public administration is related to e-government, digital government, innovation, smart city, e-service, knowledge and involve an impact on quality, transparency, trust, and public value. So, digital transformation in public administration is about a transition from analog to digital, to create new services that are more adapted to new realities in order to increase transparency and effectiveness, greater accessibility, a higher level of trust, and generally, provide a better quality of public services and citizens welfare.
Keywords: digital transformation; public administration; bibliometric analysis